Farm dam siltation and sediment source tracing in the Zeerust Swartruggens area in the north-west of South Africa. (13th September 2019) - Nde, Samuel Che; Manjoro, Munyaradzi; Mathuthu, Manny
Soil erosion and dam siltation are two serious environmental problems facing farmers in South Africa. The study aimed to assess farmers' perceptions on dam siltation and strategies employed to address it, and to assess the potential of sediment source tracing in a farming area in the north-west region of South Africa. Most of the dams in the study area were severely affected by siltation and the most important strategy used to address the problem was regular mechanical removal of the accumulated sediment. In relation to sediment tracing, lead-210 ( 210 Pb) was found to be a more effective tracer than caesium-137 ( 137 Cs) for distinguishing between surface and subsurface sediment sources. On the other hand, magnetic susceptibility offered better distinction of the sediment sources than magnetic remanence. Mass balance modelling indicated that 100% of the sampled sediment dam 1 originated from surface sources. The results reflect the complexity of sediment mobilisation processes influenced by the nature and spatial distribution of rainfall and runoff connectivity in the catchments.